Detecção de alteração no regime pluviométrico da Serra da Cantareira via modelo de espaço de Estados - Souza, Robert Luís Alves de (Universidade Federal de São Carlos, 2021)
In the period between 2014 and 2016, the Southeast region suffered from a severe drought process. According to the 2014 special insert, prepared by the National Water Agency (2014) of the Ministry of the Environment, the rainfall regime in the region presented a intense and gradual reduction of rainfall levels, which caused the water crisis, affecting the water supply in the region. Therefore, the main thesis of this report is that the rainfall regime changed, based on the fact that the rainfall behavior was far below average in different regions of the country. Thus, this work was intended to verify if this change really occurred, or was it just an extreme event. To carry out this study, data were used rainfall available on the SABESP website (http://mananciais.sabesp.com. br/Home) and adopted the state space model, as it has a large flexibility and a small prediction error. From this, we realize that, despite the variability and presence of long-term structure duration, the model was able to identify a possible change in the rainfall regime in the Cantareira System right at the beginning of the forecast, but we see that for the next steps the model was not able to identify out-of-control points.
Detection of changes in the rainfall regime of Serra da Cantareira via State Space Model
Keywords: Filtro de Kalman; Modelo espaço de Estados; Previsão; CIENCIAS EXATAS E DA TERRA::PROBABILIDADE E ESTATISTICA::PROBABILIDADE E ESTATISTICA APLICADAS